ANALISIS PENGGUNAAN METODE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS SISWA SEKOLAH DASAR: Penelitian ini bertujuan menganalisis penerapan metode Cooperative Integrated Reading and Composition (CIRC) sebagai salah satu upaya peningkatan kemampuan membaca dan menulis siswa. - Gina; Tunjungsari Sekaringtyas; Endang Wahyudiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Reading and writing literacy skills are important aspects in the academic development and daily activities of primary school students. This study aims to analyze the application of the Cooperative Integrated Reading and Composition (CIRC) method as an effort to improve students' reading and writing skills. The method used is a literature review by reviewing a number of recent studies in the last five years that are relevant. The results show that the CIRC method supports collaborative learning, integrates reading and writing activities, and builds meaningful social interactions between students in heterogeneous groups. The method has a positive impact on students' reading comprehension, writing skills, communication and critical thinking. The findings suggest that CIRC can be used effectively as a support strategy in literacy education at the primary school level.